1996
DOI: 10.1200/jco.1996.14.3.700
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive monitoring of tumor metabolism using fluorodeoxyglucose and positron emission tomography in colorectal cancer liver metastases: correlation with tumor response to fluorouracil.

Abstract: Positron emission tomography used to evaluate the uptake of FDG in tumors yields data that correlate with the antitumor effect of chemotherapy in patients with liver metastases from colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(92 citation statements)
references
References 5 publications
4
84
0
4
Order By: Relevance
“…Reference standards for the serial 18 F-FDG PET studies were the clinical response data, according to the World Health Organization (WHO) classification. In contrast to the studies of Findlay et al (10) and Bender et al (11), that study investigated absolute standardized uptake values (SUVs) and kinetic parameters and not fractional changes between baseline and follow-up scans. Even the quantitative values from the first PET study (at baseline) were predictive with respect to therapy outcome.…”
Section: Chemotherapy Response Monitoring In Advanced Colorectal Cancermentioning
confidence: 76%
See 1 more Smart Citation
“…Reference standards for the serial 18 F-FDG PET studies were the clinical response data, according to the World Health Organization (WHO) classification. In contrast to the studies of Findlay et al (10) and Bender et al (11), that study investigated absolute standardized uptake values (SUVs) and kinetic parameters and not fractional changes between baseline and follow-up scans. Even the quantitative values from the first PET study (at baseline) were predictive with respect to therapy outcome.…”
Section: Chemotherapy Response Monitoring In Advanced Colorectal Cancermentioning
confidence: 76%
“…Five studies (Table 1) reported the predictive value of 18 F-FDG PET in patients treated with chemotherapy for nonresectable colorectal cancer liver metastases (10)(11)(12)(13)(14). As early as 1996, Findlay et al (10) studied 18 patients before, at 1-2 wk after, and at 4-5 wk after 5-fluorouracil (5-FU) chemotherapy with or without interferon-a by using a nondedicated PET system with a limited resolution.…”
Section: Chemotherapy Response Monitoring In Advanced Colorectal Cancermentioning
confidence: 99%
“…FDG-PET has high sensitivity for colorectal cancer recurrence (230) and has particular utility in assessing the response in colorectal patients with hepatic metastases. For example, response to 5-FU with or without IFN was associated with lower FDG-PET SUVs at 4 to 5 weeks or with lower tumor/liver ratios at 1 to 2 or 4 to 5 weeks (227). Similarly, FDG-PET identified patients responsive to combination therapy with 5-FU and folinic acid (231) …”
Section: Fdg-pet In Oncologic Drug Developmentmentioning
confidence: 99%
“…8,9 In addition to the detection of hypermetabolic tumor, effective suppression early in the course of therapy has been linked to superior patient outcome in lymphoma and a variety of epithelial cancers. [10][11][12][13][14][15][16][17][18][19][20] When combined with CT, FDG uptake can be readily localized anatomically and, in the case of myeloma, hypermetabolic activity in intramedullary and extramedullary sites distinguished and osteolytic bone destruction recognized. 21 As part of Total Therapy 3 (see "Total Therapy 3 program"), we prospectively examined the prognostic implications of FDG-PET/CT and MRI in patients with newly diagnosed myeloma.…”
Section: Introductionmentioning
confidence: 99%